Australia’s states and territories Infection Prevention and Control programs – a comparison study - Dempsey, Kathy; Jain, Susan; Bradd, Patricia; Clezy, Kate; Greenfield, David (International Journal of Infection Control, 2024)
Background: Infection prevention and control (IPC) remains a critical component of delivering quality and safe care. However, clinician understanding of and engagement with IPC remain inconsistent (1–3). In addition, IPC governance, structure and organisation impact on clinician engagement are not well described. Available publications are limited to healthcare-associated infection (HAI) surveillance and do not reflect the broader IPC program (4–6). As Australia establishes a national coordinating body similar to a Centers for Disease Control and Prevention (CDC), a comparison of jurisdictional IPC provides essential contemporary information to inform the national body. Method: This study examined the characteristics of jurisdictional (states and territories) IPC programs in Australia and was conducted in two phases. Phase one examined outward facing websites likely to be accessed by clinicians, and phase two surveyed jurisdictional programs using a qualitative questionnaire. Results: Whilst each jurisdiction had accessible website content, this varied considerably in terms of governance, structure, content, ease of navigation, accessibility and visibility. There was a lack of national focus within jurisdictional programs and websites. Four of eight jurisdictions did not have a formal statewide IPC program at the time of the survey. Variance was reported in governance, structures, focus and program elements. Conclusion: Inconsistent IPC governance and structure demonstrates poorly aligned Australian IPC programs that may contribute to poor clinician understanding and engagement with IPC. Implementing a coordinated and consistent approach to governance, website design and layout would facilitate a consolidated approach to IPC nationally, which may facilitate clinician understanding and engagement. Shaping IPC nationally would also provide solid IPC foundations to support an Australian CDC.